Comparisons of two combined models of urban travel choices: Chicago and Dresden - Frederik Nöth; Dieter Lohse; David Boyce (European Regional Science Association (ERSA), 2002)
Methods for combining the steps of the four-step travel forecasting procedure have gained more and more interest in recent years. A comparison of two state-of-the-art models is presented: VISSUM/VISEVA by PTV AG and Technical University Dresden, Germany, and CMMC by University of Illinois at Chicago, USA. Each model is tested on large-scale networks used by practitioners at Chicago and Dresden.
Keywords: 330